1988
DOI: 10.1111/j.1365-246x.1988.tb01140.x
|View full text |Cite
|
Sign up to set email alerts
|

Canadian expedition to study the Alpha Ridge complex: results of the seismic refraction survey

Abstract: A crustal-scale seismic refraction survey has been conducted in the Arctic Ocean across the NE Alpha Ridge complex and its northern flank within the SE Makarov Basin. The data from the four reversed profiles have been analysed using 1-D and 2-D synthetic seismogram modelling schemes. Upper crustal velocities beneath these parts of the Alpha Ridge complex and Makarov Basin are surprisingly uniform at 5.0-5.2 km s-l, increasing smoothly and rapidly to ~6 . 5 km sK1 at depths of only 4 3 km. Below this level the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 72 publications
1
26
0
Order By: Relevance
“…This erratic suite is characterized by shallow marine Palaeozoic carbonates and sandstones which were widely distributed on the seabed of the Amerasia Basin by the basin's clockwise Beaufort Gyre current system. Moreover, the velocity structure of Mendeleev Ridge is similar to that shown on refraction profiles from Alpha Ridge (Jackson et al 1986;Weber 1986Weber , 1990Asudeh et al 1988;Jokat 2003), which these authors consider to have imaged oceanic volcanic rocks similar in velocity structure to the marine -volcanic Iceland -Reykjanes Ridge (see Fig. 50.4).…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…This erratic suite is characterized by shallow marine Palaeozoic carbonates and sandstones which were widely distributed on the seabed of the Amerasia Basin by the basin's clockwise Beaufort Gyre current system. Moreover, the velocity structure of Mendeleev Ridge is similar to that shown on refraction profiles from Alpha Ridge (Jackson et al 1986;Weber 1986Weber , 1990Asudeh et al 1988;Jokat 2003), which these authors consider to have imaged oceanic volcanic rocks similar in velocity structure to the marine -volcanic Iceland -Reykjanes Ridge (see Fig. 50.4).…”
mentioning
confidence: 55%
“…Modelling by Sobczak (1975a, b) suggests that about 80% of the amplitude of these anomalies can be explained by uncompensated prograded wedges of Cenozoic sediment that displaced the water mass over the underlying outer continental shelf and upper slope and that the remaining 20% or so may be caused by anomalous masses in basement, mantle ridges or carbonate banks. Vogt et al (1998a, b) Asudeh et al (1988); MR based on data presented by Lebedeva-Ivanova et al (2006) and Zamansky et al (1999); ACC from Christensen & Mooney (1995). The V p -depth functions suggest that the Alpha and Mendeleev Ridges, like the Iceland-Reykjanes Ridge, consist of basic volcanic rocks of an LIP (large igneous province) and not continental crust.…”
Section: Gravity Features That Delimit Amerasia Basinmentioning
confidence: 94%
See 1 more Smart Citation
“…Basalt cores and seismic refraction and reflection data have suggested to several workers (Weber, 1990;Asudeh et al, 1988;Jackson et al, 1986;Forsyth et al, 1986;andMuller, 1994 andJokat et al, 2007) that the A-MR constitutes a Large Igneous Province (LIP), perhaps a hot spot trace, that formed atop MORB and older oceanecontinent transitional crust (OCT) of the Amerasia Basin between about 127.5 and 89e83.5 Ma (Grantz et al, 2011b), as noted above. The volcanic rocks of the LIP are at least as young as 89 Ma, based on a 40 Ar/ 39 Ar age of basalt from near the top of the A-MR about 40 km south of the Makarov Basin (Wilfried Yokat, pers.…”
Section: Tectonic Settingmentioning
confidence: 83%
“…Scientific dredging and gravity data indicates that the Alpha and Mendeleev ridges consist of thick Upper Cretaceous alkalic basalt and diabase (Weber 1986;Muhe & Jokat 1999). Seismic refraction data showed that the Alpha Ridge has velocities and densities of mafic rocks at depth (Forsyth et al 1986), which has led most workers to conclude that the combined Alpha -Mendeleev Ridge is a volcanic hotspot or large igneous province (LIP) Forsyth et al 1986;Asudeh et al 1988). In consideration of the trans-Arctic distribution of the basaltic rocks, the Alpha-Mendeleev Ridge has been interpreted to constitute the track of a mantle-plume (hot spot) that transited the Amerasia Basin in the Late Cretaceous (Lawver & Muller 1994).…”
Section: Tectonic Evolution Of the Central Arctic Ocean Regionmentioning
confidence: 98%